Satire in Novel Tembang Talijiwo by Sujiwo Tejo - Puspo Handayani; Teguh Supriyanto; Mukh Doyin (Universitas Negeri Semarang, 2024)
An author uses different styles of language in creating his work. One of the styles languages used​ in prose literary works, such as novels, is satire. Satire is a style language used​ to mock, ridicule, or satirize customs, ideas, events in a humorous way. On this study, the researcher discussed the form of satire in the novel Tembang Talijiwo by Sujiwo Tejo. The purpose of this study was to describe the forms of satire found in the novel Tembang Talijiwo by Sujiwo Tejo. This study was expected to provide insights into stylistic analysis of language styles, especially style. The approach used​ in this study was a stylistic approach. The data source for this research was the text of the novel Tembang Talijiwo by Sujiwo Tejo. The data in this research were excerpts from the text in the novel Tembang Talijiwo suspected of containing elements of satire. The data collection technique used was heuristic technique. The data analysis technique used was hermeneutic technique. The result of this research showed the presence of irony and sarcasm in the form of satire. Irony and sarcasm were used to mock events, cases, individuals, groups, institutions, or policies. Ironic satire was used to subtly mock and criticize, while sarcasm satire is used to mock and criticize in a harsh manner.